Biomechanical analysis of take-off in spiking technique of volleyball based on anthropometric and kinematic variables - Kumar, R.; Kumar, A. (International Journal for Research in Applied Sciences and Biotechnology, 2020)
The research aimed to examine the biomechanical of take-off in volleyball's spiking technique based on anthropometric and kinematic variables. 36 junior India level players from all over India of 16 - 20 years, age group were to be selected as subjects for the study. Purposive sampling technique was used for the selection of subjects. Participants were required to deliver five relevant spiked attempts at the take-off stage as well as the perfect trial used for the analysis. Elite coaches who were available during the evaluation for grading. The take-off phase of the spike was measured based on certain criteria (10 point system). A Go Pro Hero 5 (camera) with a frequency of 240 frames per second was placed on the sagittal plane to measure kinematic parameters. Based on sequence photographs the scholar developed stick figures from which selected biomechanical variables were calculated. The stick figures, angle of different joints, the center of gravity were developed by kinovea version 0.8.27 software. Body segments (i.e., standing height, upper arm, lower arm, palm length, upper leg, and lower leg length) were measured by the anthropometric kit. The multiple regression analysis was to be used to find out the prediction of moment take-off in the spiking technique of volleyball based on anthropometric and kinematic variables at 0.05 level of significance. The results may be concluded that the regression equation is reliable as the value of R2 is 0.882. In other words, the three variable selected in this regression equation explains 88.2% of the total variability in the take-off analysis of spiking technique, which is good. Since the F-value for this regression model is highly significant, the model is reliable. At the same time, all the regression coefficients in this model are highly significant and therefore, it might be interpreted that the variable selected in the model, namely, Angle at Right knee, Angle at Right shoulder, and Center of Gravity have significant predictability in estimating the value of the take-off technique analysis of spiking. The result suggested that the center of gravity, the angle at the right knee, and the angle at the right shoulder are contributed in the take-off phase to reach a maximum vertical height in the spiking technique of volleyball. It is suggested that the results of this study provide useful information for coaches to training in lower strength & flexibility levels for attempting to increase range of joint movement and jump height to improve the spiking technique of volleyball.